Isolation and characterization of potential bacteria responsible for biodegradation of low-density polyethylene collected from garbage dump sites in Dhaka - Nahar, Abida Nurun; Farzana, Maisha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.